Efektivitas Social Media Marketing Berbasis Digital Content Sebagai Upaya UMKM Go Digital dalam Momentum Pemulihan Ekonomi di Kecamatan Gempol - miftahul huda; Nofa Ayu Prihastuti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
Covid-19 has had an impact on various sectors, especially in the economic sector, one of which is MSMEs. Many MSMEs are not ready for this condition so that they experience a decline or even bankruptcy so that the economy becomes unstable. After this pandemic, both the government and MSMEs are trying to restore the economy that has been affected by this pandemic. The purpose of this study was to determine the social media marketing based on digital content and how effective the strategy was in restoring the MSME economy. This study uses descriptive qualitative methods with data collection techniques using interviews, observation and documentation. The results of this study are a social media marketing -based digital content implemented by MSMEs covering 5 aspects, namely concept, creative, communicative, value and value. This strategy is effective in restoring the MSME economy as evidenced by an increase in sales and capital.